2019
DOI: 10.5812/semj.81500
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Satisfaction and Related Factors in Ahvazi Women in 2015

Abstract: Background: Sexual activity and its satisfaction are the most fundamental dimension of human life and attention to this is an essential component of health care standards. There are several factors involved in the progression and development of female sexual disorders. Objectives: The present study was conducted to evaluate sexual satisfaction and some of its related factors in Ahvaz city. Methods: This is a descriptive-analytical and cross-sectional study. The sampling method was convenience sampling. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In previous studies, the level of education has a significant effect on sexual satisfaction (Fallah et al, 2018;Ghahremani et al, 2017). For example, in the study by Nikbina and Afshari (2019), women with higher education had higher sexual satisfaction.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In previous studies, the level of education has a significant effect on sexual satisfaction (Fallah et al, 2018;Ghahremani et al, 2017). For example, in the study by Nikbina and Afshari (2019), women with higher education had higher sexual satisfaction.…”
Section: Discussionmentioning
confidence: 87%
“…Couples who have better dyadic sexual communication and who demonstrate better sexual assertiveness are usually more satisfied with their marital relationship (Greene and Faulkner, 2005). Aging has a significant and negative effect on the sexual quality and activity (Fallah et al, 2018;Nikbina and Afshari, 2019;Kingsberg, 2002;Sugimoto et al, 2019;Ziaee et al, 2014). Several studies have shown that marital satisfaction decreases with age, which indicates that couples with a higher average age are more likely to have more sexual problems than young couples (Cohen et al, 2014;Moshtagh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the level of education in the fertile group was higher than infertile group. Based on the results of some previous studies, it was expected that an increase in education level would be associated with an increase in sexual satisfaction (44). Also in the study of samimi et al (45).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, sexual dissatisfaction is a more frequent problem for women than men. Studies indicated that 15% to 50% of women in the world are not sexually satisfied ( 8 , 9 ). Similarly, sexual health concerns that are most commonly reported by women were related to their level of sexual desire ( 10 ).…”
Section: Introductionmentioning
confidence: 99%